Advanced fluorescence protein-based synapse-detectors - Lee, H.; Oh, W.C.; Seong, J.; Kim, J. (Frontiers Media S.A., 2016)
The complex information-processing capabilities of the central nervous system emerge from intricate patterns of synaptic input-output relationships among various neuronal circuit components. Understanding these capabilities thus requires a precise description of the individual synapses that comprise neural networks. Recent advances in fluorescent protein engineering, along with developments in light-favoring tissue clearing and optical imaging techniques, have rendered light microscopy (LM) a potent candidate for large-scale analyses of synapses, their properties, and their connectivity. Optically imaging newly engineered fluorescent proteins (FPs) tagged to synaptic proteins or microstructures enables the efficient, fine-resolution illumination of synaptic anatomy and function in large neural circuits. Here we review the latest progress in fluorescent protein-based molecular tools for imaging individual synapses and synaptic connectivity. We also identify associated technologies in gene delivery, tissue processing, and computational image analysis that will play a crucial role in bridging the gap between synapse- and system-level neuroscience. ？ 2016 Lee, Oh, Seong and Kim.
Keywords: calcium calmodulin dependent protein kinase II; fluorescent dye; green fluorescent protein; neuroligin 1; postsynaptic density protein 95; SNARE protein; synaptobrevin 2; synaptophysin; analytic method; biosensor; biotechnological procedures; brain mapping; chromophore assisted light inactivation; connectome; fluorescence analysis; gene delivery system; genetic manipulation; human; mammalian green fluorescence protein reconstitution across synaptic partner; molecular dynamics; molecular imaging; neuroimaging; neurotransmission; nonhuman; protein analysis; protein protein interaction; Review; synapse; synaptic potential; time specific tagging for the age measurement of protein